Die Innovationsfähigkeit deutscher Metropolregionen: Ein Vergleich - Hendrik Hüning; Jan Wedemeier (Wirtschaftsdienst, 2016)
Die Innovationsfähigkeit gewinnt durch die Globalisierung des Wettbewerbs zunehmend an Bedeutung. Dabei kommt den Metropolregionen eine wichtige Rolle zu. Die Autoren haben sechs deutsche Metropolregionen und aussagekräftige Innovationsindikatoren ausgewählt und untersuchen, welche dieser Regionen erfolgreich waren. – – Within the article, new key fi ndings on the innovation capability of the largest metropolitan areas in Germany are presented. One result is that the innovation capability is relatively heterogeneously distributed among the metropolitan areas. Munich possesses an enormous lead in innovation, and is one of the most innovative regions in Germany. Compared to Munich, the metropolitan areas of Berlin Brandenburg and Hamburg possess an underdeveloped innovation capability. However, through its capital function, Berlin- Brandenburg, has an excellent potential to catch up. Nevertheless, the metropolitan areas have still a long way ahead to develop their regional innovation profile and to close in the gap with the Munich region.
Keywords: O18; O31; R10; 330